PENGARUH FAKTOR DEMOGRAFI DAN KUALITAS LAYANAN TERHADAP PERSEPSI MANFAAT AMNESTI PAJAK - INDAH SARI, RAMADHANI (Jurnal Akuntansi AKUNESA, 2017)
Thisi study aims to examinei the effectiof demographic factors andiservice qualityion tax amnesty benefits perceived. Thei method usedi in this research is quantitative with questionnairei as collecting data instrument. The 92 questionnaires were distributed directly to individual taxpayers registered in KPP Pratama Surabaya. Independenti variable used in this researchi is demographic factors and service quality whilei the dependenti variablei in this research is tax amnesty benefits perceived. The results of this research analysis using Smart PLS 3 showed thatdemographic factors haven’t significant effect on tax amnesty benefits and service quality have an significant effect the tax amnesty benefits perceived. Keywords:       Perceptions, Tax Amnesty Benefits, Demographic Factors, Quality of Service